Perbandingan Pengaruh Latihan Heel Raise dan Lunges Terhadap Peningkatan Power Tungkai - Muhammad Helmi Azzam; Sri Maryati; Ucu Abdul Ropi; Isna Daniyati Nursasih (Universitas Galuh, 2024)
The purpose of this study is: to determine whether there is a significant effect of heel raise and lunges exercises on increasing leg power in students who take extracurricular activities at SMK Kopri Bekasi. The research method used is a true-experimental design, the design used is